Current Economic Crisis Effect on the Rural Community (By Ritigaha Arawa Village in Rideemaliyadda Divisional Secretariat in Badulla District Sri Lanka) - Herath Mudiyanselage, Ruwan; Upananda, D.R.P. (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2024)
Today, Sri Lanka has faced to an economic crisis, and even everyone is suffering from it. COVID pandemic was a reason to expand the crisis, but the economic policy fallowed by Sri Lanka was the main reason for the crisis. The Sri Lankan government announced Sri Lanka as an economically bankrupt country, and Sri Lanka has also stopped the resettlement of foreign loans. Exports, import restrictions, organic policy, taxation, inflation, and a lack of investors are the main reasons for spreading the crisis. The rural community is the most suffering unit of society and the objective of this paper is to examine the effect of the current economic crisis on this community. Mix methodology was used, and questionnaires, discussion, direct observations, and field visits were used to collect the data. Day to day life has been lost to the rural community with the economic crisis, and their income is not enough to fulfill their basic needs. As a result of it, some students have stopped their education, and many young people are suffering their lives with the crisis. Lost job opportunities, and the increasing price of goods are reasons to spreading malnutrition in the rural community,and the crisis has spread all over the rural community in Sri Lanka.